ChemInform Abstract: A Facile Synthesis of Functionalized 1, 2, 6, 7‐Tetrahydroimidazo[1, 5‐c]pyrimidine‐3, 5‐diones. Issue 43 (7th October 2013) - Lebed, Pavlo S.; Kos, Pavlo O.; Tolmachev, Andrey; Vovk, Mykhaylo V.; Boyko, Alexander N.; Chekotylo, Alexey
Abstract starting from 6‐azidomethyl‐2‐oxo‐3, 4‐dihydropyrimidine‐5‐carboxylates (I)